Phylogenetic relationships of the carnivorous terrestrial snail family Streptaxidae (Stylommatophora: Achatinina) in Thailand and surrounding areas of Southeast Asia. Issue 7 (15th July 2020) - Siriboon, Thanit; Naggs, Fred; Wade, Christopher M.; Jeratthitikul, Ekgachai; Tongkerd, Piyoros; Jirapatrasilp, Parin; Panha, Somsak; Sutcharit, Chirasak
Abstract : Southeast Asia boasts a high diversity of carnivorous terrestrial snails in the family Streptaxidae. Six genera are now recognized in this region, mainly classified by the traditional characters of shell morphology, especially the configuration of the apertural dentition and eccentric shell shape. More recently, genital characters have been used to reveal new species and genera. However, the monophyly of genera and the relationships among different genera and species have not yet been determined. In this regard, we constructed a molecular phylogeny of 89 streptaxid specimens from Thailand, Malaysia and Laos, representing 36 morphospecies in six genera using the COI and 16S rRNA mitochondrial DNA genes. Our findings revealed at least 10 clades with distinct geographic distributions. These clades were both concordant and discordant with traditional classification based on shell morphology. Both Discartemon and Perrottetia are monophyletic with strong statistical support, and congruent with the morphological classification. However, Carinartemis was retrieved as paraphyletic, and Haploptychius and Oophana were retrieved as polyphyletic. Within the genus Discartemon, the D. roebeleni species group shows differentiation between the mainland peninsula and the islands in Southern Thailand. This study is the first evolutionary hypothesis from molecular evidence helping us to assess the status of Thai streptaxid genera, revealing high species diversity amongst the Thai taxa and further complementing our understanding of the biogeographic relationships among different lineages.